Formulasi serta Uji Aktivitas Antioksidan dan Tabir Surya Krim Ekstrak Aseton Biji Buah Alpukat - Suradnyana, I Gede Made; Juliadi, Debby; Suena, Ni Made Dharma Shantini (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2023)
The skin often exposed to sunlight and pollution requires treatment with products that protect it from UV radiation and free radicals. Avocado seeds are known to have the potential as a sunscreen and have good antioxidant activity. This study aims to prove the antioxidant and sunscreen activity of acetone avocado seed extract, produce a cream formula that functions as a sunscreen and antioxidant for the skin, and determine the correlation of extract concentration with the activity of avocado seed acetone extract sunscreen cream. Testing of sunscreen and antioxidant activity was carried out in vitro. The results showed that the SPF and IC50 values of the extract were 39.636 and 10.36 ppm, respectively. The SPF value of F1, F2, and F3 creams were 1.859 ± 0.152, 2.941 ± 0.065, and 3.629 ± 0.053, respectively. The SPF value of the three creams was significantly different (p<0.05), and there was a significant (p<0.001) and strong correlation between the concentration of the extract and the SPF value. The IC50 values of formula F1, F2, and F3 were 9.74 ppm, 7.02 ppm, and 6.86 ppm, respectively. Based on these results, it can be concluded that acetone extract from avocado seeds has a high level of sunscreen activity and very strong antioxidant activity. The cream has an SPF value under the category of low protection level and very strong antioxidant activity. A significant and strong correlation exists between the extract's concentration and the cream's SPF value.